Analysis of Factors Associated with the Incidence of Stunting in Toddlers in the Working Area of Ketapang II Health Center, East Kotawaringin Regency - Sartika, Dewi; Sanyoto, Didik Dwi; Febriana, Silvia Kristanti Tri; Adhani, Rosihan; Suhartono, Eko (Newinera Publisher, 2024)
National data from the 2021 Indonesian Nutritional Status Survey (SSGI) states that the stunting rate in Indonesia, which is 24.4%, has decreased by 2.8% so that in 2022 it will be 21.6%. The prevalence of stunting in Central Kalimantan Province in 2022 is 26.9%. This states that the prevalence of stunting in Central Kalimantan ranks 11th highest in Indonesia. SSGI results the stunting prevalence of East Kotawaringin Regency in 2020 reached 27.49% and decreased in 2021 to 23.24%. This paper aims to determine the relationship between parenting, education level, income, food intake, IMD history, and exclusive breastfeeding history with the incidence of stunting in toddlers at Ketapang II Health Center. The research method is observational analytic using a cross sectional approach with a population of 447 people obtained 90 people as samples using purposive sampling techniques. The research instrument is a questionnaire. Dependent variable: stunting. Independent variables: parenting, education level, income, food intake, IMD history, and exclusive breastfeeding history. Bivariate analysis using chi square and multivariate using multiple logistic regression. The results showed that there was a relationship between parenting (p = 0.000), education level (p = 0.001), income (p = 0.025), food intake (p = 0.000), BMI history (p = 0.018), and exclusive breastfeeding history (p = 0.000), with the incidence of stunting in toddlers. Parenting variables are most associated with the incidence of stunting in toddlers (Exp(B) = 23,560). This study concluded that there is a relationship between parenting, education level, income, food intake, IMD history, and exclusive breastfeeding history with the incidence of stunting.